The green mile - Valdes, David; Darabont, Frank ([S.l.] : Warner Brothers, 2000)
Miracles happen in unexpected places, even in the death-row cellblock at Cold Mountain Penitentiary. There John Coffey, a gentle giant of prisoner with supernatural powers, brings a sense of spirit and humanity to his guards and fellow inmates.
n.2 is acquisition for KPI (Kelab Pencinta Ilmu)
Screenplay, Frank Darabont
Starring: Tom Hanks, Michael Clarke Duncan
Keywords: Supernatural in motion pictures